1999
DOI: 10.1023/a:1026688610468
|View full text |Cite
|
Sign up to set email alerts
|

O(d,d)-invariance in Inhomogeneous String Cosmologies with Perfect Fluid

Abstract: In the first part of the present paper, we show that O(d, d)-invariance usually known in a homogeneous cosmological background written in terms of proper time can be extended to backgrounds depending on one or several coordinates (which may be any space-like or time-like coordinate(s)). In all cases, the presence of a perfect fluid is taken into account and the equivalent duality transformation in Einstein frame is explicitly given. In the second part, we present several concrete applications to some four-dime… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…[10−11] Khastgir and Kumer studied the black holes solutions with O(2, 2) duality symmetry for spacedependent background fields, [12] Demaret and Pietro analysed the O(d, d)-invariance in inhomogeneous string cosmologies with perfect fluid. [13] Moreover, Gasperini discussed dilaton phenomenology and pre-big bang scenario in string cosmology. [14−15] In priveous paper, we found that power law solutions containing singular points could be generated through O(2, 2) transformations.…”
Section: Introductionmentioning
confidence: 99%
“…[10−11] Khastgir and Kumer studied the black holes solutions with O(2, 2) duality symmetry for spacedependent background fields, [12] Demaret and Pietro analysed the O(d, d)-invariance in inhomogeneous string cosmologies with perfect fluid. [13] Moreover, Gasperini discussed dilaton phenomenology and pre-big bang scenario in string cosmology. [14−15] In priveous paper, we found that power law solutions containing singular points could be generated through O(2, 2) transformations.…”
Section: Introductionmentioning
confidence: 99%